Implementation of Building Automation System on Smart Stove to Prevent Fire in Apartment based on Virtuino - Muhammad Naufal Eka Syahban; Misbah Misbah (G-Tech: Jurnal Teknologi Terapan, 2025)
The increasing price of land in urban areas makes apartments an alternative housing in urban areas. Apartments as housing cannot be separated from basic human needs, namely eating, drinking, and sleeping. To meet food and drink needs, a stove is definitely needed as a cooking tool. The use of a stove also affects the security of the apartment itself considering the different characters of the residents/tenants. Negligence of the owner or tenant will cause losses for the management or the owner himself. From this problem, a smart stove was created that can detect LPG gas leaks and can provide information to security officers on the same floor using a wifi signal. The system designed uses ESP32 as a system processor and several sensors to support fire detection such as fire sensors and LPG sensors (MQ 2). The use of Virtuino as an IOT (Internet Of Things) device makes it easier for apartment security officers and apartment owners/tenants to monitor LPG gas leaks and the presence or absence of fire and provide early warnings in the form of information sent to Virtuino if a fire occurs in the monitored area.